Normative theory of international relations and the 'mackerel war' in the North East Atlantic. (September 2021) - Gray, Tim
Abstract: This paper is a normative analysis of the so-called 'mackerel war' - the long-running dispute between Iceland, the Faroes, and Greenland on the one hand, and the EU and Norway on the other, over the distribution of the mackerel quota in the North East Atlantic fishery. Most researchers on the mackerel war have focused on the 'facts' of the dispute, explaining the actions of the states in behavioural terms, often employing game theory techniques. This study adopts a normative interpretation which analyses state actions in moral terms. Normative theory in international relations divides into two approaches – communitarianism which endorses state morality; and cosmopolitanism which endorses global morality – and the study shows that Iceland, the Faroes and Greenland have largely adopted the communitarian approach, while the EU and Norway have largely adopted the cosmopolitan approach. This is the first time a normative analysis of the mackerel conflict has been systematically conducted, and the paper uses it to identify and evaluate the ethical arguments used by the parties to justify their actions, thereby providing a fresh interpretation of the controversy which aims to get to its heart. The paper's verdict on the quality of those ethical arguments is that both communitarian and cosmopolitan protagonists can claim some moral credibility, but they each lose some of that credibility by exaggerating the moral strength of their own case and exaggerating the moral weakness of their opponent's case. Such exaggeration not only devalues the moral currency of the discourse on the mackerel war, but also prolongs the duration of the conflict by reinforcing the intransigence of the opposed parties.